Pengaruh Flash Sale dan Live Streaming Terhadap Impulse Buying Behavior Pada Platform TikTok - Ratna Gumilang, Risa; Sumiati, Ai; Tresnadi, Aris (Coopetition : Jurnal Ilmiah Manajemen, 2024)
The development of technology and the internet has transformed societal lifestyles, with TikTok leveraging this trend through TikTok Shop, integrating entertainment and shopping with features like flash sales and live streaming to drive sales and influence consumer behavior. This study aims to examine the impact of flash sales and live streaming on impulse buying behavior on the TikTok platform. Using a quantitative approach with a survey of 400 respondents from Generation Z (aged 18-27) who have purchased through flash sales and live streaming on TikTok. Data analysis employed multiple linear regression. The findings indicate that both flash sales and live streaming significantly and positively influence impulse buying behavior. These strategies collectively form a robust approach to stimulate impulse buying: flash sales create purchase urgency, while live streaming enhances direct consumer engagement. This research offers valuable insights for TikTok sellers in optimizing flash sales and live streaming to enhance sales through impulse buying behavior.